(untitled) (Academicia Globe: Inderscience Research, 2023)
The kidneys are made up of about a million filtering units called nephrons. Each nephron includes a filter, called the glomerulus, and a tubule. The glomerulus filters the blood, and the tubule returns needed substances to the blood and removes wastes and extra water, which become urine. Nephrotic syndrome usually happens when the glomeruli are damaged, allowing too much protein to leak from the blood into the urine.